1977
DOI: 10.2466/pms.1977.45.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Females Judged by Attractiveness of Partner

Abstract: 30 male and 30 female students rated a female photographed with either an attractive or an unattractive male on 8 bipolar adjective scales. The female was rated more positively when paired with an attractive male than when paired with an unattractive male on 6 of the 8 adjective scales. There were no significant differences between the ratings given by male and female subjects and no significant interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…On the basis of signaling theory, both sexes possess traits that contribute to their social influence and mate value but are not easily perceivable [20]; therefore, both men and women should publicly advertise hard-to-fake perceptible signals (including mates) that broadcast possession of these hidden traits. As noted, previous research shows that both males and females who are paired with attractive partners are more positively evaluated by both same and opposite sex observers [7], [8]. Although the proposed extension of signaling theory, consistent with other research [32], predicts that increased (or primed) mating motives may augment an individual’s propensity to flaunt, it also predicts that an individual will flaunt or conceal regardless of his or her relationship status.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the basis of signaling theory, both sexes possess traits that contribute to their social influence and mate value but are not easily perceivable [20]; therefore, both men and women should publicly advertise hard-to-fake perceptible signals (including mates) that broadcast possession of these hidden traits. As noted, previous research shows that both males and females who are paired with attractive partners are more positively evaluated by both same and opposite sex observers [7], [8]. Although the proposed extension of signaling theory, consistent with other research [32], predicts that increased (or primed) mating motives may augment an individual’s propensity to flaunt, it also predicts that an individual will flaunt or conceal regardless of his or her relationship status.…”
Section: Introductionsupporting
confidence: 66%
“…Observers rated a man as least favorable when he was associated with an unattractive confederate. Strane and Watts [8] found that women who were paired with attractive men in photographs were rated more favorably than women who were paired with unattractive men. Waynforth [12] and Vakirzis and Roberts [13] explicitly demonstrated that the variable of importance in these cases is the relative attractiveness of the putative partner.…”
Section: Introductionmentioning
confidence: 99%
“…Research on impression management notes that individuals may act to increase associations with high‐status or successful others to make themselves look better (i.e., ‘basking in reflected glory’, see Cialdini & De Nicholas, 1989, Dijkstra, Cillessen, Lindenberg, & Veenstra, 2010). Indeed, individuals seem to be evaluated more positively if they are associated with a physically attractive partner (e.g., Sigall & Landy, 1973; Strane & Watts, 1977). In contrast, research on social stigma indicates that an individual's mere physical proximity to stigmatized (i.e., low‐status) others may negatively affect opinions and attributions regarding that individual (e.g., Argo & Main, 2008; Hebl & Mannix, 2003).…”
Section: Popularity Contagionmentioning
confidence: 99%
“…Attractive persons are more likely to receive assistance from others (14,131), are more capable of iniluencing others (88, 89) and of resisting peer pressures (1). They lend social enhancement to less attractive partners (107,108,113), report more satisfaction with their personality and leadership ability (15), are judged less harshly when committing transgressions (32, 33, 95), and achieve higher grades (109). In the field of mental health, physically attractive female patients are given less serious diagnoses, are accorded more attention, and are hospitalized fbr shorter periods of time (41).…”
Section: Review Of the Literaturementioning
confidence: 99%